2016
DOI: 10.20473/fmi.v51i4.2855
|View full text |Cite
|
Sign up to set email alerts
|

Papaya Seed Extract Lowers Sperm Concentrations, Motility and Viability in Male Mice

Abstract: ABSTRAKIndonesia adalah negara berkembang dengan penduduk padat, sehingga pemerintah menjalankan program KB (Keluarga Berencana)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…The results of this study are in accordance with previous research conducted by Wiryawan et al (2016) that there was a decrease in the concentration of spermatozoa in mice given papaya seed extract orally. This is predicted because the alkaloid content is estrogenic which results in a decrease in the hormone testosterone by inhibiting the gonadotropin glands (GnRH) to inhibit LH and FSH secretion in the anterior pituitary.…”
Section: Discussionsupporting
confidence: 93%
“…The results of this study are in accordance with previous research conducted by Wiryawan et al (2016) that there was a decrease in the concentration of spermatozoa in mice given papaya seed extract orally. This is predicted because the alkaloid content is estrogenic which results in a decrease in the hormone testosterone by inhibiting the gonadotropin glands (GnRH) to inhibit LH and FSH secretion in the anterior pituitary.…”
Section: Discussionsupporting
confidence: 93%
“…2,3 Extract of papaya seed showed an antifertility effect in mice by lowering sperm concentration, motility, and viability. 4,5 Extract of Stelechocarpus burahol also has an antifertility effect in male mice 6 . Ethanol extract of Dalbergia sissoo Roxb stem bark has anti-spermatogenic activity, 7 Taraxacum officinale also has anti-spermatogenic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Sertoli cells mediate the process of spermiation, namely the cytoplasm is released from the spermatids and mature sperm is released into the lumen of the seminiferous tubules, this process is also influenced by endocrine hormone regulation. This alkaloid content can interfere with this process because it is estrogenic which can interfere with the spermiogenesis process (Wiryawan et al 2016). Based on the above review, it can be concluded that the ethanol extract of papaya leaves (Carica papaya L.) can affect the histopathological picture of the testicles of young adult mice (Mus musculus).…”
Section: Discussionmentioning
confidence: 99%